A questão racial, o poder e a política: uma análise acerca das candidaturas de ativistas negros(as) nas eleições municipais de 2020 em Aracaju (SE) - Santos, Carlos Eduardo Trindade (2023)
This research work aims to analyze the sociological conditions that impacted the electoral results obtained by the candidacies of black people in the 2020 municipal election for the position of councilor, in the municipality of Aracaju (SE). Based on a bibliographical review and the application of a questionnaire with 7 (seven) activists, we seek to broaden our understanding of the social, political, cultural and institutional barriers that make it difficult for black people to access spaces of power. Its results point to difficulties of various kinds, not only financial – admittedly one of the biggest obstacles – which require initiatives to change and renegotiate the democratic order as a whole, making it, in fact, participatory and diversified from a cultural point of view.